Maqasid Shariah in the guidelines for iddah of women upon husband's death / Fatimah Salleh ... [et al] - Salleh, Fatimah; Sahari, Noorul Huda; Ab Manan, Siti Khadijah; Abdullah, Che Zahrah; Yahya, Zaharah (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Iddah is a period of mourning for a woman whose husband has passed on during which time she has to adhere to certain rules set by the Islamic law. Adherence to this rule is a form of devotion for the preservation of lineage and descent while at the same time expressing sadness. In addition, this order has also been applied to protect the welfare and rights of women after the death of the husband. Adherence to certain laws and regulations by women whose husband has passed away, has long been outlined by Islamic scholars. However, the reality of today's life requires many women to leave home for work or other family-related matters. This scenario creates a polarization in society where a woman whose husband dies needs to mourn and at the same time meet the needs of the family. The general public is still unclear. The implementations and practices are seen as inconsistent and not uniformed due to their misunderstandings and possibly even confusion of their practices during this mourning state of iddah. This study aims to identify the rules to be followed for women whose husband has passed on, with regard to dressing, travelling, and practising with their co-workers in accordance with shariah or maqasid shariah objectives. This study uses qualitative method based on two approaches, namely doctrinal mazhab method based on contemporary sects and fiqh approaches. The findings of this study indicate that there is a need for more detailed guidelines and waqi'e within the scope of the syariah jurisprudence for community reference in adhering to the rules and laws of the state. This takes into account the current contexts in order to avoid misunderstandings or confusion among the public.